The Effectiveness of Music Therapy on Hand Function in Patients With Stroke: A Systematic Review of Randomized Controlled Trials - Huang, Wen-Hao; Dou, Zu-Lin; Jin, Hui-Min; Cui, Ying; Li, Xin; Zeng, Qing (Frontiers in Neurology, 2021)
Objective: This study aims to evaluate the efficacy of music-supported therapy for stroke patients' hand function. Methods: The databases used included Cumulative Index to Nursing and Allied Health Literature (CINAHL), MEDLINE, PubMed, Embase, Music Index, and Google Scholar. Studies published between January 2010 and August 2020 were included. The searching key terms included “music-supported therapy,” “music therapy,” “hand function,” “hand dysfunction,” “stroke,” “ischemic,” and “hemorrhagic.” Randomized controlled trials or controlled trials involving adults who have hand function problems caused by stroke are included in this study. The methodological quality and risk of bias of the included studies were rated by two independent assessors under the guidance of Cochrane collaboration's risk of bias tool. Results: Twelve studies that met the inclusion criteria were included in this study. Totally, the data included 598 stroke patients (345 male, 253 female) with recruited time from 1.7 months to 3 years, and the mean age of the participants were 61.09 years old. Based on the Cochrane risk of bias tool, study quality ranged from three to seven out of seven points. Compared with the control group, outcomes including hand strength, range of joint motion, dexterity of hands, arm function, and quality of life were significantly superior with music-supported therapy. Five studies reported improved dexterity of hands, and one study reported the improvement of range of motion and strength of patients' hands, which supported the therapy has positive effects on patients' hand function and improving their quality of life after the therapy. The therapy ranged over a period of 4–8 weeks, with an average duration of 30 min/session and an average of three times per week. Conclusion: Based on the results, music-supported therapy could be a useful treatment for improving hand function and activities of daily living in patients with stroke, especially for patients within 6 months after stroke. However, the low certainty of evidence downgrades our confidence to practice in hospital. More and more randomized controlled trials and larger sample sizes are required for a deeper review.